2011
DOI: 10.1136/thx.2011.158972
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in outcomes for non-small cell lung cancer: the influence of clinical characteristics and features of the local lung cancer service

Abstract: BackgroundThe treatment given to patients with lung cancer and survival vary between and within countries. The National Lung Cancer Audit (NLCA) linked to Hospital Episode Statistics was used to quantify the extent to which these outcomes are influenced by patient features and/or hospital facilities and performance indicators. Methods All patients with a histological diagnosis of non-small cell lung cancer (NSCLC) were included. Logistic regression was used to quantify the independent influence of features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 21 publications
9
68
0
1
Order By: Relevance
“…For England and Wales, the National Lung Cancer Audit has shown significant regional inequalities in resection rates and other active treatment rates [55][56][57]. Several Norwegian studies have shown regional variations in resection rates and risk factors for post-operative mortality, as well as in the radiotherapy and chemotherapy regimens used [58][59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…For England and Wales, the National Lung Cancer Audit has shown significant regional inequalities in resection rates and other active treatment rates [55][56][57]. Several Norwegian studies have shown regional variations in resection rates and risk factors for post-operative mortality, as well as in the radiotherapy and chemotherapy regimens used [58][59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…The 2016 National Lung Cancer Audit reported that the range of patients with non-small cell lung cancer (NSCLC) who received surgical treatment varied from 5% to 36% across different trusts. 3 Previous studies have also demonstrated that a person can be up to 51% more likely to receive thoracic surgery for lung cancer if they are first diagnosed in a thoracic surgical centre, 14,15 and this effect is most pronounced in surgical centres with the largest lung cancer populations.…”
Section: Stagingmentioning
confidence: 99%
“…In a UK regional study (Billing et al, 1996) showed that the mean total delay from presentation to operation for Non Small Cell Lung Cancer (NSCLC) was 109 days. Rich (Rich et al, 2011) also from UK found that resection rates and subsequently survival data were better when patients had easier access to thoracic surgical facilities. In India where conditions are not very different from ours, Chandra (Chandra et al, 2009) found the median symptom to initiation delay to be 185 days.…”
Section: Discussionmentioning
confidence: 97%